Single nucleotide polymorphisms in obesity-related genes and all-cause and cause-specific mortality: a prospective cohort study - Ruczinski Ingo; Strickland Paul; Huang Han; Thuita Lucy; Christo Dana K; Chang Howard H; Gallicchio Lisa; Clipp Sandra; Helzlsouer Kathy J (BMC, 2009)
Abstract Background The aim of this study was to examine the associations between 16 specific single nucleotide polymorphisms (SNPs) in 8 obesity-related genes and overall and cause-specific mortality. We also examined the associations between the SNPs and body mass index (BMI) and change in BMI over time. Methods Data were analyzed from 9,919 individuals who participated in two large community-based cohort studies conducted in Washington County, Maryland in 1974 (CLUE I) and 1989 (CLUE II). DNA from blood collected in 1989 was genotyped for 16 SNPs in 8 obesity-related genes: monoamine oxidase A (MAOA), lipoprotein lipase (LPL), paraoxonase 1 and 2 (PON1 and PON2), leptin receptor (LEPR), tumor necrosis factor-α (TNFα), and peroxisome proliferative activated receptor-γ and -δ (PPARG and PPARD). Data on height and weight in 1989 (CLUE II baseline) and at age 21 were collected from participants at the time of blood collection. All participants were followed from 1989 to the date of death or the end of follow-up in 2005. Cox proportional hazards regression was used to obtain the relative risk (RR) estimates and 95% confidence intervals (CI) for each SNP and mortality outcomes. Results The results showed no patterns of association for the selected SNPs and the all-cause and cause-specific mortality outcomes, although statistically significant associations (p < 0.05) were observed between PPARG rs4684847 and all-cause mortality (CC: reference; CT: RR 0.99, 95% CI 0.89, 1.11; TT: RR 0.60, 95% CI 0.39, 0.93) and cancer-related mortality (CC: reference; CT: RR 1.01, 95% CI 0.82, 1.25; TT: RR 0.22, 95% CI 0.06, 0.90) and TNFα rs1799964 and cancer-related mortality (TT: reference; CT: RR 1.23, 95% CI 1.03, 1.47; CC: RR 0.83, 95% CI 0.54, 1.28). Additional analyses showed significant associations between SNPs in LEPR with BMI (rs1137101) and change in BMI over time (rs1045895 and rs1137101). Conclusion Findings from this cohort study suggest that the selected SNPs are not associated with overall or cause-specific death, although several LEPR SNPs may be related to BMI and BMI change over time.